Cyclodimerization of Stilbenes and Styrenes Catalyzed by Heteropolyacid Supported on Silica - Alesso, E. (2000)
Several stilbenes and styrenes have been treated with heteropolyacid] (HPA) supported over silice. The compounds obtained were characterized by 1 H and 13 C- NMR and the yields were compared with those obtained using H2SO4 (c) and ethyl poliphosphate (PPE).